KATEKESE SAKRAMEN TOBAT DALAM MENINGKATKAN PEMAHAMAN UMAT DI STASI SANTO PETRUS PAULUS PANAEN PAROKI SANTA MARIA DE LA SALETTE MUARA TEWEH - Eka Resti; Romanus Romas; Silvester Adinuhgra (Sekolah Tinggi Pastoral Tahasak Danum Pambelum Keuskupan Palangkaraya, 2021)
This study aims to determine how important catechesis is in improving the understanding of Catholics, especially the Catechism of the Sacrament of Penance. Catechism as a way to give understanding to the people about the teachings that exist in the Catholic Church. Through this study, it is hoped that Catholics can understand what the Sacrament of Penance is so that the faith of the people will grow and develop. This type of research is a qualitative research with a descriptive approach. Data obtained by using interviews and documentation. The research was carried out in May 2021 at the St. Petrus Paulus Panaen Station, Santa Maria De La Salette Muara Teweh Parish. There were 7 informants consisting of 1 fellow Pastor, and 6 people. The data analysis technique uses the Miles and Huberman model which consists of 3 stages, namely reduction, data presentation, and drawing conclusions.